The centrality of ethical utterances within professional narratives. (February 2022) - Neu, Dean; Saxton, Gregory D.; Everett, Jeffery; Rahaman, Abu
This study examines the centrality of ethics within editorials published in the Canadian Institute of Chartered Accountants' professional journal, CA Magazine, over the 1912 to 2010 period. Starting from the twin assumptions that editorials speak about appropriate professional behavior using a variety of words such as 'ethics, ' 'conduct, ' and 'codes, ' and that appropriate professional behavior is situational, we use topic modeling techniques to identify these dimensions of ethical discourse. We then use social network analysis methods to map the position and centrality of ethics within the editorials across time. The results show that enunciations about appropriate professional conduct are broader than simply enunciations using the word 'ethics'. The results also highlight that ethical utterances become more central, not less central, over time.